2020
DOI: 10.1016/j.envpol.2020.115021
|View full text |Cite
|
Sign up to set email alerts
|

Differential micropollutants bioaccumulation in European hake and their parasites Anisakis sp.

Abstract: Organisms are exposed to various stressors including parasites and micropollutants. Their combined effects are hard to predict. This study assessed the trophic relationship, micropollutants bioaccumulation and infection degree in a host-parasite couple. Carbon and nitrogen isotopic ratios were determined in hake Merluccius merluccius muscle and in its parasite Anisakis sp.. Concentrations of both priority (mercury species and polychlorinated biphenyls congeners) and emerging (musks and sunscreens) micropolluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Muscle stable isotopic ratios were measured with a Thermo Scientific® Delta V Advantage mass spectrometer coupled to a Thermo Scientific® Flash EA1112 elemental analyzer following routine protocol of the Plateforme Spectrometrie Ocean (https://www-iuem.univ-brest.fr/delta-v-plus-eagb/?lang=en) and used in previously published paper (e.g. Mille et al, 2020;Timmerman et al, 2020).…”
Section: Carbon and Nitrogen Stable Isotope Analysismentioning
confidence: 99%
“…Muscle stable isotopic ratios were measured with a Thermo Scientific® Delta V Advantage mass spectrometer coupled to a Thermo Scientific® Flash EA1112 elemental analyzer following routine protocol of the Plateforme Spectrometrie Ocean (https://www-iuem.univ-brest.fr/delta-v-plus-eagb/?lang=en) and used in previously published paper (e.g. Mille et al, 2020;Timmerman et al, 2020).…”
Section: Carbon and Nitrogen Stable Isotope Analysismentioning
confidence: 99%
“…Dogs with heartworm disease (Dirofilaria immitis, a nematode feeding directly on the host's blood) also exhibited lower serum levels of PCBs, OCPs, and PAH compared with non-infected dogs (Henríquez-Hernández et al, 2016). Similar findings were found for PCBs, but not for musk fragrances (Mille et al, 2020).…”
Section: Consequences Of Parasites As Contaminant Sinks On the Pollut...mentioning
confidence: 68%
“…Similar findings have been reported for organic pollutants (mainly persistent ones), but studies remain scarce because of analytical challenges in providing accurate methods to quantify chemical analytes, such as their metabolites, from a limited amount of biological samples. For instance, polychlorobiphenyls (PCBs) levels were significantly higher in acanthocephalans than in perch (Brázová et al, 2012), in intestinal cestodes, Caryophyllaeus laticeps, than in their host (bream, Abramis brama, Brázová et al, 2021), and in the intestinal nematode, Anisakis sp., than in European hake (Mille et al, 2020). This bioaccumulation was observed for organochlorine pesticides (OCPs), polybrominated diphenyl ethers, phthalates, and polycyclic aromatic hydrocarbons (PAHs) in acanthocephalans compared with the muscle of their chub host but not for pyrethroid insecticides (Molbert et al, 2020) or musk fragrances (Mille et al, 2020).…”
Section: Accumulation Of Pollutants In Parasites a Widespread Phenomenonmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, no significant differences in parasite abundance were found, although female catfish harboured a greater number of G. osculata cestodes than males. Mille et al 46 showed that larger male hake harboured a greater number of endoparasites than smaller females. They explained that this difference could be caused by sexual dimorphism in fish size.…”
Section: Discussionmentioning
confidence: 99%